HUBUNGAN KARAKTERISTIK IBU DENGAN KEJADIAN ABORTUS DI RSU MUHAMMADIYAH MEDAN TAHUN 2020 - Siti Arofah Siregar; Rapida Saragih (Universitas Prima Indonesia, 2021)
According to the World Health Organization (WHO), 15-50% of maternal deaths are caused by abortion. Data shows the possibility of a fairly high percentage, approximately 15-40% the number of known occurrences on mothers who already stated positively pregnant, and 60-75% of abortion occurs before the pregnancy reaches 12 weeks. This research investigates the relationship between the mother’s characteristics with the abortion case in the RSU Muhammadiyah. The investigation was conducted in a cross-sectional analysis. The population is 42 mothers who experienced abortion in the RSU Muhammadiyah based on medical record year 2020. Statistical analysis using chi-square with the p-value of age, parity, and education parameters are 0,002, 0.017, and 0.004 respectively. This data showed that there was a relationship between age, parity, and education with abortion cases in RSU Muhammadiyah Medan. This report might be useful for the government and stakeholders in controlling the abortion case in Medan.